Celibate marriages in late antique and Byzantine hagiography : the lives of Saints Julian and Basilissa, Andronikos and Athanasia, and Galaktion and Episteme /: the lives of Saints Julian and Basilissa, Andronikos and Athanasia, and Galaktion and Episteme. (2011) - Alwis, Anne P (Anne Priyani)
No abstract available